2022
DOI: 10.3390/lubricants10020023
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss, Thermodynamics, SEM, and Electrochemical Studies on N-2-Methylbenzylidene-4-antipyrineamine as an Inhibitor for Mild Steel Corrosion in Hydrochloric Acid

Abstract: The use of N-2-methylbenzylidene-4-antipyrineamine as an acid corrosion inhibitor for mild steel surfaces in hydrochloric acid is discussed in this article by means of weight loss, electrochemical impedance spectroscopy (EIS), and scanning electron microscopy (SEM) methods. The experimental findings exhibited that N-2-methylbenzylidene-4-antipyrineamine is a significant corrosion inhibitor for the mild steel in 1.0 M HCl solution and that its protection efficiency touches the peak at 5 × 10–4 M, exhibiting 91.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…It can be observed that the temperature produced an increase in V corr , even in the presence of PILs, which was attributed to desorption phenomena of the inhibiting macromolecules. In addition, it is shown that the lowest V corr values were obtained at C INH of 175 ppm, indicating that a higher amount of PIL macromolecules can form a more homogeneous protecting film that reduces the diffusion of sulfate ions toward the metallic surface [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the temperature produced an increase in V corr , even in the presence of PILs, which was attributed to desorption phenomena of the inhibiting macromolecules. In addition, it is shown that the lowest V corr values were obtained at C INH of 175 ppm, indicating that a higher amount of PIL macromolecules can form a more homogeneous protecting film that reduces the diffusion of sulfate ions toward the metallic surface [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion inhibition property of the prepared coating is examined using the acid immersion tests on the A36 steel by weight loss method 22,32 . The weight of bare steel and CaF 2 ‐impregnated alkyd resin‐coated steel is noted before and after immersing in acid and is summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of inhibition, these plots reveal a single depressed capacitive semicircle. [ 58 ] Upon introducing the thiophen derivative, the impedance modulus of the system rises to its maximum, underlining the inhibitor's concentration‐dependent influence on the corrosion process. To interpret these results, we employed a comparable circuit model, as depicted in Figure 7b, [ 59 ] encompassing the solution resistance (Rs ${R}_{{\rm{s}}}$), charge transfer resistance governing the interfacial corrosion process (Rct ${R}_{\mathrm{ct}}$), and a constant phase angle element (CPE).…”
Section: Resultsmentioning
confidence: 99%